Utilization of Telemedicine Services for National Health Insurance Participants at Primary Health Facilities - Salesika; Sitorus, Rico Januar; Syakurah, Rizma Adlia (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
Health service through undirect contact/telemedicine can be a solution for national health assurance (JKN) participants to get health service in the primary health care facilities (FKTP) during the COVID-19 pandemic. However, telemedicine utilization in FKTP is still low compared to physical contact. This study aims to analyze the utilization of telemedicine services by JKN participants in accessing health services in FKTP Musi Rawas Regency. Quantitative research with a cross-sectional design was used. Data was obtained from July 2021 to October 2021 from JKN participants registered at the FKTP in Musi Rawas Regency using questionnaires online (Google Form) and offline. The sample was selected using a consecutive sampling technique. Data was analyzed using univariate, bivariate, chi-square, and multivariate methods, with logistic regression tests and p-values of 0.05 and 95% CI, respectively. Most respondents (73.9%) did not use telemedicine services at the FKTP Musi Rawas Regency. The utilization of telemedicine services of JKN participants FKTP was affected by trust, education, length of travel time to health services, JKN membership category, behavior of health workers, socialization, use of cellular phones, and internet access (p<0.05). The confidence (p-value < 0.000 (OR 53.3; 95% CI: 23.55-120.64)) and socialization (p-value < 0.000 (OR: 7.167; 95%CI: 3.339-15.384)) were the most influence of the utilization of telemedicine services by JKN participants at the FKTP Musi Rawas Regency. The utilization of telemedicine services at the FKTP of Musi Rawas Regency has not been optimal. Massive socialization is needed by FKTP, BPJS Health, and local government regarding the use of health services through telemedicine at FKTP, which will be accompanied by the development of telemedicine applications.